"Primum, non nocere": The Epidemiology of Toxigenic Clostridioides difficile Strains in the Antibiotic Era-Insights from a Prospective Study at a Regional Infectious Diseases Hospital in Eastern Europe - Lidia Oana Stămăteanu; Claudia Elena Pleşca; Ionela Larisa Miftode; Aida Corina Bădescu; Doina Carmen Manciuc; Mihnea Eudoxiu Hurmuzache; Manuel Florin Roșu; Radu Ștefan Miftode; Maria Obreja; Egidia Gabriela Miftode (MDPI AG, 2024)
Clostridioides difficile infection (CDI), though identified nearly five decades ago, still remains a major challenge, being associated with significant mortality rates. The strains classified as hypervirulent, notably 027/NAP1/BI, have garnered substantial attention from researchers and clinicians due to their direct correlation with the severity of the disease. Our study aims to elucidate the significance of toxigenic Clostridioides difficile (CD) strains in the clinical and therapeutic aspects of managing patients diagnosed with CDI. We conducted a single-center prospective study, including patients with CDI from north-eastern Romania. We subsequently conducted molecular biology testing to ascertain the prevalence of the presumptive 027/NAP1/BI strain within aforementioned geographic region. The patients were systematically compared and assessed both clinically and biologically, employing standardized and comparative methodologies. The study enrolled fifty patients with CDI admitted between January 2020 and June 2020. Among the investigated patients, 43 (86%) exhibited infection with toxigenic CD strains positive for toxin B genes (tcdB), binary toxin genes (cdtA and cdtB), and deletion 117 in regulatory genes (tcdC), while the remaining 7 (14%) tested negative for binary toxin genes (cdtA and cdtB) and deletion 117 in tcdC. The presence of the presumptive 027/NAP1/BI strains was linked to a higher recurrence rate (35.56%, p = 0.025), cardiovascular comorbidities (65.1% vs. 14.2%, p = 0.016), and vancomycin treatment (55.8% vs. 14.3%, p = 0.049). The findings of our investigation revealed an elevated incidence of colitis attributed to presumptive 027/NAP1/BI. Despite the prevalence of the presumptive 027 strain and its associated heightened inflammation among the patients studied, no significant differences were observed regarding the clinical course or mortality outcomes.